2019
DOI: 10.1109/tkde.2018.2822727
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Data Truthfulness and Privacy Preservation in Data Markets

Abstract: As a significant business paradigm, many online information platforms have emerged to satisfy society's needs for person-specific data, where a service provider collects raw data from data contributors, and then offers value-added data services to data consumers. However, in the data trading layer, the data consumers face a pressing problem, i.e., how to verify whether the service provider has truthfully collected and processed data? Furthermore, the data contributors are usually unwilling to reveal their sens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In [17], users can decide to publish data items according to the aggregation opinions, who can adjust the parameters to make a balance between data sharing and privacy protection, but the privacy threshold setting was random. Niu and Zheng et al in [18] proposed an effective combination of authenticity and privacy protection, which adopted encryption and signature to effectively maintain identity protection and data confidentiality; however, it was difficult to adapt to the real data service market. Pham and Yeo et al in [19] designed a context-aware trust management scheme and proposed a secure and flexible framework to manage trust and privacy; however, the protocol was complex and the practicability was low.…”
Section: B Privacy and Multiple Factorsmentioning
confidence: 99%
“…In [17], users can decide to publish data items according to the aggregation opinions, who can adjust the parameters to make a balance between data sharing and privacy protection, but the privacy threshold setting was random. Niu and Zheng et al in [18] proposed an effective combination of authenticity and privacy protection, which adopted encryption and signature to effectively maintain identity protection and data confidentiality; however, it was difficult to adapt to the real data service market. Pham and Yeo et al in [19] designed a context-aware trust management scheme and proposed a secure and flexible framework to manage trust and privacy; however, the protocol was complex and the practicability was low.…”
Section: B Privacy and Multiple Factorsmentioning
confidence: 99%
“…In [30], Acquisti et al indicated that privacy valuations are highly dependent on subtle scenarios and are inconsistent. Niu et al [31] proposed an effective data market security model, which can guarantee data authenticity and protect privacy. Nget et al [32] considered a practical personal data trading framework that strikes a balance between money and privacy.…”
Section: Related Workmentioning
confidence: 99%
“…Previous papers have reported research on data marketplaces and data exchange platforms where data are traded as exchangeable economic goods [18,19]. These studies have explored game theory [20], privacy models [21,22], a market model for innovative collaboration [5], a secure model using blockchain [10], pricing mechanisms of data [23,24], and the complex network approach to conceptualize data exchange platforms [25]. Therefore, considering data matching in the data marketplace is a natural extension of these previous works.…”
Section: Introductionmentioning
confidence: 99%